The barley powdery mildew protein kinase C gene, pkc1 and pkc-like gene, are differentially expressed during morphogenesis. - Zhang, Z; Priddey, G; Gurr, S (2001)
summary Protein kinase C agonist assays revealed the phorbol ester, phorbol 12-myristate 13-acetate, invoked germling morphogenesis and enhanced PKC activity in Blumeria graminis. No antagonist of mildew PKC activity was found but the data fuelled a hunt for powdery mildew pkc genes. Oligonucleotides, designed on the basis of conserved ATP-binding and kinase domains within the catalytic core of eukaryotic protein kinase proteins, were used as primers to amplify chromosomal and cDNA fragments from the barley powdery mildew fungus graminis. Three kinase gene fragments were isolated (pkc1, pkc-like and cpka) and the full length genomic sequences of the mildew pkc and pkc-like genes were determined by 'step down' PCR. RT-PCR transcript profiles showed the three genes to be differentially regulated during germling morphogenesis.